Management of end-stage vascular access failure patients: a retrospective analysis - Gameiro,Joana (2018)
Vascular access (VA) dysfunction is an important cause of morbidity and mortality in the hemodialysis (HD) population. Regardless of the increasing prevalence of HD patients with complex VA, the definitions of VA failure (VAF) or end-stage VA failure (ES-VAF) are still being discussed and there is no current guideline that provides recommendation for solving the problem of complicated vascular access. The aim of this study was to review the management approach for resuming the continuity of RRT in patients with problematic vascular accesses, based on our center experience. In a retrospective analysis of 30 patients with VAF or ES-VAF over an 11-year period, twenty patients were transferred to peritoneal dialysis (PD), seven patients remained in HD after the placement of a non-standard site VA and three patients had a renal transplant (RT). In half of these patients, the initial therapeutic option eventually failed, leading to multiple reinterventions and RRT changes. Mean survival was 47 ± 32.7 months. Ten patients died, the majority within the first year of VAF diagnosis. The management of end-stage renal disease patients includes vessel preservation, the combination of RRTs to extend life expectancy and VA care to maintain long-term function. Our approach stratifies patients according to exhausted VA sites in order to plan for RT, transition to PD or alternative VA site management. This allows for better management of the VAF patient and highlights the need to individualize patient care.